Angiopoietin-1 mediates inhibition of hypertension-induced release of angiopoietin-2 from endothelial cells - Korff, Thomas; Nobiling, Rainer; Feldner, Anja; Augustin, Hellmut; Hecker, Markus (Cardiovascular research, 2012)
Abstract Aims Adequate endothelial cell stimulation is a prerequisite for the adaptive remodelling of macro- and microvessels
Gesehen am 29.10.2018